Determination of the Optimum Hydraulic Retention Time in Two-Stage Anaerobic Fluidized Bed Bioreactor for Landfill Leachate Treatment - Eli Prasetyo; Hanifrahmawan Sudibyo; Wiratni Budhijanto (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Leachate in Indonesian landfill sites poses a high risk to the surrounding environment should there be leakage in the accumulating ponds. Anaerobic digestion is an attractive option to clean up leachate, mostly due to the affordability of its operational cost. To enhance the efficiency of leachate digestion, anaerobic microbes were immobilized on the surface of natural zeolite powder. The powder was fluidized in a mesophilic anaerobic fluidized bed reactor (AFBR) for more stable biofilm formation. The AFBR scheme was split into two stages, with the first stage dominated by the acidogenic process and the second stage dominated by the methanogenic process. The dominating microbes in each stage were provoked by pH control to maintain the first stage acidic at pH 5-5.5 and the second stage neutral at pH 7-7.5. The first stage was run at five different hydraulic retention times (HRTs), while the second stage was run at three different HRTs to determine the optimum HRT for each stage. For acidogenic AFBR with HRTs of 5 days and 2.5 days, the VFA concentration profile increased for a longer period compared to the other HRTs. The COD removal efficiency at steady state was almost identical for all HRTs. For methanogenic AFBR, all three HRTs showed an identical rate of biogas formation at steady state.